Improving Language Literacy Skills of 5 and 6-Year-Old Children Through Picture Story Method at School - Magay, Deky; Lanny, Elizabeth (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2022)
This study aims to improve the language literacy skills of children aged 5-6 through the media of illustrated story series in Shabat Getasan school children of Semarang Regency. This research is urgent to determine the improvements to children's language literacy skills. This research is a class action research (PTK). This research consists of two cycles, and each cycle is held in two meetings. The subjects of this study were 12 children of Shabat Getasan School, Semarang Regency. The data was collected through observation and documentation. The observation results before the action (pre-cycle) showed language skills in children with Good criteria of 0%, and cycle I of children's oral language skills who entered the Good criteria of 0% and cycle II of 80-90%. The results showed that the media of picture stories could improve language literacy skills in children aged 5-6 years. Thus, it can be concluded that the media of picture stories can improve language literacy skills in Shabat Getasan school children, Semarang Regency.